Isländische Nationalbewegung im 19. Jh. (ca. 1880-1918) - Piotrowski, Bernard (Folia Scandinavica Posnaniensia, 2007)
The article presents the main development phases of the independence movement in Iceland (ca 1800-1918). The Icelanders’ activities took various political and social forms: concern for the native language, literature and culture; parliament activity (althing); support for industrial development and more favourable social structures; formation of political parties and social organisations; attempts to persuade the Danish to issue more advantageous legislation for the Icelanders.